Gambaran Tingkat Pengetahuan Tentang Resiko Kehamilan Pada Remaja Putri Di Posyandu Wilayah Kerja Puskesmas Penumping - Wulandari, Dwi; Hermawati, Hermawati (CV. Utami, 2026)
Teenage pregnancy remains a public health problem occurring in various regions, caused by juvenile delinquency. Adolescents aged 10–19 years are at risk of pregnancy, which can lead to physical, psychological, and social impacts. Objective: To determine the level of knowledge regarding the risks of pregnancy among adolescent girls at the community health posts (Posyandu) in the working area of Penumping Community Health Center. Methods: This study employed a descriptive quantitative method. A total of 59 respondents were selected using stratified random sampling, with sampling in each stratum conducted through simple random sampling. The instrument used was a questionnaire. Results: The characteristics of respondents based on age showed that most were aged 13–15 years, totaling 25 respondents (42.4%). Based on education level, most respondents were junior high school students, totaling 24 respondents (40.7%). Based on sources of information, most respondents obtained information from health education sessions, totaling 24 respondents (40.7%). The level of knowledge of the respondents showed that 39 respondents (66.1%) had good knowledge. Conclusion: The level of knowledge of adolescent girls regarding the risks of teenage pregnancy was in the good category, with scores ranging from 75–100%.